Association Between Insulin Resistance and Hyperandrogenism in Women with PCOS. A Cross-Sectional Clinical Study - Shazia, Shazia Ashraf, Rahila Naz, Nazneen Akhtar, Naila Javed, Syeda Nosheen Zehra, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovary syndrome (PCOS) is one of the common endocrine disorders that is typified by both reproductive and metabolic dysfunctions with hyperandrogenism and insulin resistance being the major manifestations. A combination of these two factors is central to disease manifestation and progression. Objectives: To assess the relationship between biochemical and clinical hyperandrogenism and insulin resistance in PCOS women. Methods: This cross-sectional clinical study included one hundred women diagnosed with PCOS. Clinical hyperandrogenism was assessed using the modified Ferriman–Gallwey (mFG) score, while biochemical hyperandrogenism was evaluated by measuring serum total testosterone, sex hormone-binding globulin (SHBG), and calculating the free androgen index (FAI). Insulin resistance was estimated using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Participants were stratified into insulin-resistant and non–insulin-resistant groups based on a predefined HOMA-IR cutoff. Associations between insulin resistance and androgen parameters were analyzed using correlation analyses, group comparisons, and multivariable linear regression. Results: Insulin-resistant women reported much higher mFG scores, high total testosterone and FAI and lower SHBG levels than non-insulin-resistant participants (P value < 0.05). The clinical and biochemical markers of hyperandrogenism were significantly and negatively correlated with HOMA-IR, whereas SHBG had a positive correlation with HOMA-IR. Insulin resistance was observed to be a predictive independent variable of high androgen levels even after controlling the age and body mass index. Conclusion: hyperandrogenism in PCOS women has a close relationship with insulin resistance, which is an independent isomer of androgen overproduction. Insulin resistance can be characterized and managed early in the life of the affected individuals and this may enhance their metabolic, as well as reproductive outcomes. Keywords: Polycystic Ovary Syndrome, Insulin Resistance, Hyperandrogenism, HOMA-IR, Testosterone, DHEA-S.